2017
DOI: 10.1002/cbdv.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Ecotype Variation of Methyl Eugenol Content in Tea Tree (Melaleuca alternifolia and Melaleuca linariifolia)

Abstract: Methyl eugenol is a natural phenylpropanoid compound found in a wide range of plants used for food, flavouring, cosmetics, and health-care. As a suspected rodent carcinogen, methyl eugenol may also be harmful to humans when present in significant concentrations. Consequently, its level has been restricted in some foodstuffs and cosmetics for some markets. In order to assess the potential to breed uniformly low methyl eugenol cultivars for an essential oil crop, tea tree, the source of 'Oil of Melaleuca, terpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Such genetic variation could be induced by geographic or environmental isolation of different populations adapted to local conditions and with limited gene flow among them (Kleessen et al 2012;Prunier et al 2017). Several studies documented the geographical patterns of intraspecific differentiation in plant morphology (Pucher et al 2015;Upadhyaya et al 2017) and phytochemical profiles (Bellomo and Fallico 2007;da Silva et al 2017;Masetti et al 2017;Shepherd et al 2017). We hypothesize that the observed trade-off between carotenoids and tocopherols associated with geographical origin could be explained by differential expression of some genes involved in carotenoid, chlorophyll and tocopherol synthesis.…”
Section: Relationships Between Accessions and Trait Correlationsmentioning
confidence: 90%
“…Such genetic variation could be induced by geographic or environmental isolation of different populations adapted to local conditions and with limited gene flow among them (Kleessen et al 2012;Prunier et al 2017). Several studies documented the geographical patterns of intraspecific differentiation in plant morphology (Pucher et al 2015;Upadhyaya et al 2017) and phytochemical profiles (Bellomo and Fallico 2007;da Silva et al 2017;Masetti et al 2017;Shepherd et al 2017). We hypothesize that the observed trade-off between carotenoids and tocopherols associated with geographical origin could be explained by differential expression of some genes involved in carotenoid, chlorophyll and tocopherol synthesis.…”
Section: Relationships Between Accessions and Trait Correlationsmentioning
confidence: 90%
“…Existing studies have shown that isocalamenediol, α-asarone, β-asarone, methyl eugenol, isoeugenol methyl ether, camphor, anethol, 2,4-di-tert-butylphenol, linalool, and asarylaldehyde are the 10 main medicinal components in KXS VOCs which have good medicinal effects. For example, β-asarone and α-asarone have good effects as antidepressants, and in the treatment of anti-senile dementia and memory improvement; methyl eugenol has anesthetic effects 31,37. For the reason that quantitative analysis of the main volatile medicinal substances which provides a basis for the study of the medicinal substance basis of KXS.…”
mentioning
confidence: 99%
“…Such genetic variation could be induced by geographic or environmental isolation of different populations adapted to local conditions and with limited gene flow among them (Kleessen et al 2012;Prunier et al 2017). Several studies documented the geographical patterns of intraspecific differentiation in plant morphology (Pucher et al 2015;Upadhyaya et al 2017) and phytochemical profiles (Bellomo and Fallico 2007;da Silva et al 2017;Masetti et al 2017;Shepherd et al 2017). We hypothesize that the observed trade-off between carotenoids and tocopherols associated with geographical origin could be also explained by differential expression of the specific genes involved in either carotenoid or tocopherol synthesis.…”
mentioning
confidence: 91%